ANALYSIS OF LEADERSHIP STYLES AND ORGANIZATIONAL CULTURE IN EFFORTS TO IMPROVE EMPLOYEE PERFORMANCE EDUCATION AND CULTURE OF PESAWARAN DISTRICT - Aprianis .; Yosi Yulia (Saburai International Journal of Social Sciences and Development, 2020)
The purpose of the research in this thesis is to examine the influence of Leadership Style and Organizational Culture on employee performance in the Department of Education and Culture of Pesawaran District. This study uses a survey research method with 65 respondents. This analysis uses qualitative analysis and data processing using the SPSS program. The results showed that the Leadership Style had a positive effect on employee performance with the effect of a contribution of 69.4%. Furthermore, Organizational Culture also has a positive influence on employee performance with a contribution of 68.3%. The regression test shows that there is a positive influence between Leadership Style and Organizational Culture on employee performance. The magnitude of the influence of the two variables X1 and X2 on Y is 78.9%, the remaining 21.